2019
DOI: 10.1038/s41392-019-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compound cinobufotalin potently induces FOXO1-stimulated cisplatin sensitivity by antagonizing its binding partner MYH9

Abstract: In this study, we present novel molecular mechanisms by which FOXO1 functions as a tumor suppressor to prevent the pathogenesis of nasopharyngeal carcinoma (NPC). First, we observed that FOXO1 not only controlled tumor stemness and metastasis, but also sensitized NPC cells to cisplatin (DDP) in vitro and in vivo. Mechanistic studies demonstrated that FOXO1-induced miR-200b expression through the GSK3β/β-catenin/TCF4 network-mediated stimulation of ZEB1, which reduced tumor stemness and the epithelial–mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…In previous studies, miRNAs have been widely reported to be regulated by various transcription factors. 39 , 40 , 41 , 42 Sp1 belongs to a famous Sp transcription family, which also includes Sp2 , Sp3 , and Sp4 , and it has been importantly proven to modulate essential biological processes such as cell growth, 43 differentiation, 44 and apoptosis and carcinogenesis. 45 For many cancer patients, elevated Sp1 expression is considered as an adverse prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, miRNAs have been widely reported to be regulated by various transcription factors. 39 , 40 , 41 , 42 Sp1 belongs to a famous Sp transcription family, which also includes Sp2 , Sp3 , and Sp4 , and it has been importantly proven to modulate essential biological processes such as cell growth, 43 differentiation, 44 and apoptosis and carcinogenesis. 45 For many cancer patients, elevated Sp1 expression is considered as an adverse prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Non-muscle myosin heavy chain IIA (MYH9) is involved in many biological processes, including cell migration, adhesion, division, polarity, and morphogenesis. 3 MYH9 is dysregulated and serves as an oncogene in many cancers; [4][5][6][7][8][9][10] however, its expression is positively associated with a good prognosis in patients with head and neck squamous cell carcinomas. 11 Moreover, researchers have reported that MYH9 promotes cell invasion and metastasis in gastric cancer, 12,13 facilitates cell growth and metastasis in colorectal cancer and pancreatic cancer, 14,15 and induces drug resistance in neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…In prior study, we have shown that SPEN induces mir-465-3p expression, However, the mechanism by which SPEN regulates miR-4652-3p expression has not been elucidated. It is well known that transcript factor-mediated miRNA transcription expression has been widely documented in tumors 11 , 20 , 25 . In this study, we first predicted the possible transcription factors binding to the miR-4652-3p promoter.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) area class of small (17–23 nucleotides) noncoding RNAs that silence mRNA molecules through a degradation or translational inhibition process. They participate in various biological processes, including tumorigenesis and metastasis 11 13 . Multiple miRNAs have been found to play key roles in regulating the expression of various critical genes during the development of human tumors 4 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%